Photo-oxidative damage to isolated rat liver mitochondria induced by phenothiazines - T. Rodrigues; P.A.F. Faria; F.S. Pessoto; C.G. Santos; I.L. Nantes (São Paulo State University (UNESP), 2005)
Photosensitization is a well-known side-effect of phenothiazines that could involve photochemically promoted oxidative damage to mitochondria, leading to the impairment of metabolic functions and apoptosis. In this work, for the first time, we investigated the effects of photoexcited thioridazine (TR), trifluoperazine (TFP) and fluphenazine (FP) on isolated rat liver mitochondria. Under UV irradiation, the presence of these phenothiazines led to a dose-dependent lack of the respiratory control ratio. These effects were not accompanied by significant swelling and oxidation of protein thiol groups but were accompanied by lipid peroxidation. Lycopene and sorbate, well-known quenchers of singlet oxygen and triplet species, respectively, were ineffective at protecting mitochondrial lipids against the damage promoted by the excited phenothiazines, suggesting that photochemically-produced cation radicals were the prooxidant species. Corroborating this proposal, butylated hydroxytoluene (BHT) completely inhibited the lipid peroxidation induced by UV irradiation in the presence of phenothiazines. These novel results make a significant contribution to the understanding of the photochemical properties of phenothiazines in biological systems.